Good Governance di Perguruan Tinggi Islam - Umar Sidiq (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
Currently colleges are under pressure from the government to show maximum results for the funds that have been given by the government. Good university governance is still a hot topic to talk about. There are six things that must be considered in managing a good college, namely: governance, management of academic programs, human resources, funding, university assets, and quality assurance. This fact is interesting to study further, how the efforts of state Islamic universities to develop good governance in order to develop the quality of education in their institutions, especially after institutional transformation from IAIN / STAIN to UIN. Keywords: Good governance, Islamic College, Transformation.